HARVESTER ANT AS AN IMPORTED COMMODITY FOR ANT LOVERS IN INDONESIA WHICH BECOMES A PEST AND CAUSES ENVIRONMENTAL DAMAGE - Rosnawati, Emy; Hermansyah, Malik Muhammad (ANTIS PUBLISHER, 2024)
This research is to analyze whether Harvester Ants can be categorized as animals that are harmful to the environment to be imported into Indonesia and why the import of Harvester Ants which are considered pests in other countries is still running so far and can still enter Indonesia. This research uses a normative juridical method and this research uses a statute approach or statutory approach (using a systematic and grammatical interpretation). The results of this study are that the import of harverster ant is a prohibited import because this ant is a very dangerous and very invasive ant for other ants and the surrounding environment which is feared to cause crop failure for local farmers, causing damage to the environment and ecosystem.